The Social Reality of Smartphones in Adolescent Social Interaction (Oratio Directa, 2022)
This study examines how smartphones shape the social reality and interaction patterns of adolescents. It uses a qualitative descriptive approach based on interviews and observation. The source identifies three 13-year-old junior-secondary students, but does not report the study period, sampling procedure, interview protocol, consent process, or systematic analysis technique. Media dependency theory and the social construction of reality provide the analytical framework. The findings show that smartphones support schoolwork, information seeking, rapid communication, and interaction across distance. At the same time, participants describe reduced sensitivity to their immediate surroundings, preference for mediated interaction, distraction, and difficulty balancing screen use with face-to-face communication. These accounts indicate a negotiated, rather than uniformly negative, transformation of adolescent interaction. Because the evidence is limited to a small, incompletely documented case, it cannot establish prevalence, addiction, or causal effects. The study highlights the need for contextual digital literacy, self-regulation, family and school guidance, and future research using transparent ethical procedures and measurable patterns of use.
Keywords: Social reality; Smartphones; Social interaction; Adolescents; Media dependency